Influence of Age and sex on body weight and some body linear measurements of Extensively Reared wad Goats in Derived Savannah zone of Nigeria - Ojedapo, L.O; Adedeji, T.A.; Olayeni, T.B.; Adedeji, O.S.; Abdullah, A.R.; Ojebiyi, O.O. (2007)
Body weight and body linear measurement (Diagonal body length, Height-at-withers, sac pelvic width, Heart girth) of 259 West African Dwarf (WAD) goats (both sexes) in three age groups (Kid, yearling and Adult) were measured. The least square means for body weight were 6.40, 10.5 and 18.9 kg for kid, yearling and Adult respectively. Means of other body linear measurements also vary within each age group. The variables measured vary positively with age of the animals and the correlations of body weight with diagonal body length, Height at whither, sac-pelvic width and heart girth were high, positive and significant (p